Kritik Riwayat Penafsiran Israiliyat Al-Tabari Tentang Kisah Nabi Yusuf Dalam Surat Yusuf Ayat 24 - Mawardi Mawardi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Criticism of the History of Israiliyat At-Tabari's Interpretation of the Story of the Prophet Yusuf in Surah Yusuf Verse 24This paper aims to critically analyze the sources of Israiliyyat Tafsir Al-Tabari against Yusuf verse 24 in the book Jami' al-Bayan Fi Tafsir al-Qur'an. The method used in this study is a qualitative descriptive method and is included in the category of library search research. The use of qualitative descriptive methods because of its suitability with the subject and focus of research. This study found: the quality of the Israiliyat narrations in Tafsir al-Tabari about the story of the Prophet Yusuf and the temptation of a woman used to interpret Surah Yusuf (12): 24, some of the narrations are odd and not in line with Islamic law, and some of them are who are mauquf (silenced), because they are not supported by the arguments of the Qur'an or hadith. This study found that the quality of the Israiliyat narrations in Tafsir al-Tabari about the story of the Prophet Yusuf and the temptation of a woman used to interpret Surah Yusuf verse 24, some of the narrations are odd and not in line with Islamic law, and some are mauquf ( silenced), because it is not supported by the arguments of the Qur'an or hadith. Al-Tabari himself is essentially inconsistent with his aim of interpreting the verses of the Qur'an from narrations that have no clear path of history, especially regarding Surah Yusuf verse 24, where he instead quotes Israeli stories whose quality is not guaranteed. So it is feared that the knowledge obtained regarding these israiliyat stories obscures the true meaning of the original meaning stated by the Qur'an or the Sunnah of the Prophet Muhammad